ARTISTIC SERVICE OF REPETITIONS IN THE LYRICS OF M. JUMANAZAROVA AND P. MIRZABAEVА - Aliyeva Khurliman Rakhmanbergenovna (Western European Studies, 2024)
In this article the issue of the role of repetitions in the creation of the lyrical heroic character is studied on the example of the poets M.Jumanazarova and P. Mirzabaeva
Keywords: poetic; literary language; literary style